IDENTITAS DIASPORA PEREMPUAN INDIA DALAM CERITA PENDEK WANITA AMERIKA-INDIA Hujuala Rika Ayu Sastra Inggris Fakultas Bahasa dan Seni Universitas Negeri Surabaya ayuhujualarika@yahoo.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract: This paper discusses the identity of Indian women in diaspora in the short stories  of  two  American  Indian  women  writers,  Bharati  Mukherjee  and  Jhumpa Lahiri. This paper uses the theories of diaspora and diasporic identity. Leaving the home land and entering the host land have created ambiguous situations for Indian diasporic women. However, although they have similar aims of immigrating to the host  land,  their  ways  and  perspectives  of  inserting  themselves  to  the  host  land  are different. They are not only challenged by the reality of adapting and adopting the cultural values of the host land but also at the same time maintaining the values of the  old  world.  These  female  characters  have  particular  roles  of  creating  ‘the  old world’  in  the  host  land  and  balancing  the  dynamics  of  the  two  worlds.  Efforts  of adapting self to the new world and given roles of maintaining the old values in the new world have somehow modified the ideas of women’s identities in newland. Keywords: diaspora, Indian diasporic women, ambivalence, diasporic identity